Narrative Construction of Morality in Adolescence Among Typically Developing and Violence-Exposed Youth. (December 2017) - Pasupathi, Monisha; Wainryb, Cecilia; Bourne, Stacia; Posada, Roberto
In this article, we explore two different perspectives on what narratives reveal about differences in moral agency construction across contexts. We focus on contexts that vary in violence exposure because such exposure has implications for the way youth develop a sense of moral agency. We elicited narratives about harm-doing from three samples of youth: a North American typical sample, a North American juvenile delinquent sample, and a sample of Colombian displaced youth. The latter two samples have in common a history of significant exposure to violence. Our results show reductions in psychological content (e.g., references to emotions, thoughts, and desires) and increases in reciprocity and vengeful themes among violence-exposed youth, particularly in the context of narrating their own harmful actions. We consider the meaning of these differences from two different perspectives about the meaning of narratives.